Secondary Metabolites and Eco-Friendly Techniques for Agricultural Weed/Pest Management - Fabrizio Araniti; Marco Landi; Vito Armando Laudicina; Maria Rosa Abenavoli (Plants, 2021)
In agro-ecosystems, pests (insects, weeds, and other plant’s parasites) compete with crops for edaphic resources, negatively affecting quality and crop yields [...]